Analisis Putusan Hakim Terhadap Perkara Anak Sebagai Pelaku Tindak Pidana Kejahatan Seksual - Nanik Sutarni (Fakultas Hukum Universitas Boyolali, 2023)
Sexual crimes against children will generally have a negative impact on children's development, both psychologically and in other developments. The objectives of this study are: 1.) Knowing the judges' judgment in making decisions on sexual violence against children in criminal case Number 3 / Pid.Sus.Anak / 2018 / PN.Byl, 2.) Knowing whether the judge's decision at the Boyolali District Court in case Number 3 / Pid.Sus.Anak / 2018 / PN.Byl are in accordance with the provisions of Law Number 35 of 2014 concerning Child Protection. In compiling this study, the authors used a normative juridical legal approach. The conclusion that the authors get from this research is that the purpose of punishment is not to give sorrow to the perpetrator of a criminal act but is preventive, educative and corrective in nature, so the criminal charges imposed on the child as stated in the ruling are deemed less appropriate and fair and less appropriate. with the level of child error and contrary to the sense of justice in society. The defendant's actions were obscene acts against the victim's child, referring to article 82 paragraph (1) of Law Number 35 of 2014 concerning Child Protection. However, according to the author, the judge should have dropped Article 81 paragraph (1) and pointed out Article 82 paragraph (1) of Law Number 35 of 2014 concerning child protection because from the facts it is clear that the defendant's act was more an act of sexual intercourse which was previously committed as an obscene act. firstly, the elements of the article have been fulfilled for the defendant's act which was consciously committed and had bad faith / intention to commit the act to the victim's child long before the act was committed and of course it could incriminate the defendant.